2023
DOI: 10.3390/molecules28072982
|View full text |Cite
|
Sign up to set email alerts
|

Cis-Nerolidol Inhibits MAP Kinase and NF-κB Signaling Pathways and Prevents Epithelial Tight Junction Dysfunction in Colon Inflammation: In Vivo and In Vitro Studies

Abstract: Inflammation of the GI tract leads to compromised epithelial barrier integrity, which increases intestine permeability. A compromised intestinal barrier is a critical event that leads to microbe entry and promotes inflammatory responses. Inflammatory bowel diseases that comprise Crohn’s disease (CD) and ulcerative colitis (UC) show an increase in intestinal permeability. Nerolidol (NED), a naturally occurring sesquiterpene alcohol, has potent anti-inflammatory properties in preclinical models of colon inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…3-Hydroxy-2-butanone can serve as the characteristic compound of BZH, while methyl 2-nonynoate and nerolidol can serve the same purpose for CLU. Nerolidol is used medicinally to treat colon cancer and can also be used in cosmetics and food regulators ( Chan et al, 2016 ; Raj et al, 2023 ; Zhao et al, 2023 ). 1-Nonanol, 1-hexanol, 2-methylpropan-1-ol, and 1-heptanol can be used as characteristic compounds of QJ and XC.…”
Section: Resultsmentioning
confidence: 99%
“…3-Hydroxy-2-butanone can serve as the characteristic compound of BZH, while methyl 2-nonynoate and nerolidol can serve the same purpose for CLU. Nerolidol is used medicinally to treat colon cancer and can also be used in cosmetics and food regulators ( Chan et al, 2016 ; Raj et al, 2023 ; Zhao et al, 2023 ). 1-Nonanol, 1-hexanol, 2-methylpropan-1-ol, and 1-heptanol can be used as characteristic compounds of QJ and XC.…”
Section: Resultsmentioning
confidence: 99%
“…LPS-stimulated cells can activate ERK, JNK and p38 and subsequently act on their substrates to affect the activity of various transcription factors, thus regulating the expressions of diverse cytokines, including TNF, IL-6 and IL-8. Therefore, it can trigger an inflammatory response in the colon through ERK, JNK and p38 [ 61 , 62 ]. In previous studies, several herbal ingredients, such as Ganoderma lucidum polysaccharide, were shown to relieve colitis through the MAPK signaling pathway [63] .…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect on the NF-κB pathway can significantly suppress the secretion of inflammatory indicators [35][36][37]; the inhibitory effect on the NF-κB pathways is considered an effective approach to control the occurrence and development of inflammatory diseases [38].…”
Section: Discussionmentioning
confidence: 99%